Pengaruh Pengungkapan Emisi Karbon, Eco-Efficiency, dan Inovasi Hijau Terhadap Nilai Perusahaan Pada Perusahaan Sektor Energi di Indonesia - Tantra, Arda Raditya; Nurani, Bulan Karima; Ani, Dewi Ari (Faculty of Economic and Business Universitas STIKUBANK, 2026)
This study examines the impact of carbon emission disclosure, eco-efficiency, and green innovation on firm value among energy sector companies listed on the Indonesia Stock Exchange during 2022-2024. Using purposive sampling, 26 companies were selected based on specific criteria, resulting in 78 observations over the three-year period. The research employs panel data regression analysis with fixed effect model, using Tobin's Q as the proxy for firm value. Carbon emission disclosure is measured using the CDP framework with 18 disclosure items, eco-efficiency is assessed through ISO 14001 certification ownership, and green innovation is evaluated using four indicators based on the OECD framework. The results reveal that green innovation has a significant positive effect on firm value, indicating that Indonesian capital market investors place premium valuations on companies investing in environmental innovation. However, carbon emission and eco-efficiency show no significant impact on firm value. These findings suggest that while sustainability disclosure remains voluntary in Indonesia and lacks standardized frameworks, market participants are more responsive to tangible innovations that demonstrate competitive advantages and regulatory risk mitigation. Simultaneously, all three variables significantly influence firm value, confirming the relevance of comprehensive sustainability practices in value creation.